(untitled) (Academicia Globe: Inderscience Research, 2024)
This article delves into the essence of Romanticism in English poetry, focusing on its key themes of nature, emotion, and the sublime. Through a historical lens, it explores the socio-political context that gave rise to the Romantic movement and examines the ways in which poets of this era reimagined the role of nature in literature. Emphasizing the importance of subjective experience, the article delves into the emotional depths of Romantic verse, analyzing how poets like Wordsworth, Coleridge, Keats, and Shelley captured the complexities of human emotion in their work. Furthermore, it investigates the concept of the sublime and its significance in Romantic literature, shedding light on the profound impact of the natural world on the human psyche. Through close readings and comparative analysis, the article illustrates the diverse approaches to Romantic poetry and highlights its enduring influence on subsequent literary movements and contemporary culture. Ultimately, it argues that Romanticism continues to offer valuable insights into the human condition, reminding us of the timeless power of nature, the depth of emotion, and the boundless potential of the human spirit.